(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The aim of the research is to know the impact of the process of selecting human resources on the organizational culture in the Iraqi Ministry of Health. The descriptive statistical analytical method was used on the sample members from the health sector, which numbered 229 from the staff working in the ministry. The research found a direct impact on the selection of human resources in The Ministry of Health focuses on organizational culture, and the research recommended the need to work on developing good programs and standards for the process of attracting, selecting and appointing human resources to work in order to be in line with the organizational culture in the health institution.